Transforming Our World: The Role of Collections in Education for Sustainable Development - Mar Gaitán; Alejandra Nieto-Villena; Arabella León; Indra Ramírez; Ester Alba (Heritage, 2025)
The TOWCHED project explores how arts and heritage-based educational methodologies can support sustainable development by enhancing key transversal competencies in learners, particularly children and youth. In response to the global challenges outlined in the sustainable development goals (SDGs), this project promotes inclusive and participatory approaches to education that foster social cohesion, intercultural understanding, and civic engagement. Partnering with museums, TOWCHED develops cross-curricular pedagogical interventions, such as experiential, blended, and collection-mediated learning, that link cultural heritage with contemporary social and environmental concerns. These approaches aim to strengthen creativity, critical thinking, collaboration, and self-awareness. TOWCHED demonstrates that heritage collection-based education can play a vital role in transforming schools and other learning environments into hubs for sustainable, lifelong learning. By embedding cultural expression and heritage into educational practices, the project offers a compelling model for empowering individuals to navigate and shape a more equitable and interconnected world. This paper has two aims. First, we introduce TOWCHED, an interdisciplinary project recently funded by the Horizon Europe program of the European Union to preserve and promote education for sustainability in the heritage context. Second, we introduce a set of tools related to the project.